Is Pepsin a Reliable Marker of Laryngopharyngeal Reflux? A Systematic Review. (September 2017) - Calvo-Henríquez, Christian; Ruano-Ravina, Alberto; Vaamonde, Pedro; Martínez-Capoccioni, Gabriel; Martín-Martín, Carlos
Objective: Laryngopharyngeal reflux (LPR) is a common illness of otolaryngology visits. Over the past few years, pepsin has become a promising marker of LPR. The objective of the present research is to analyze the existing literature using pepsin as a diagnostic tool of LPR through a systematic review. Data Sources: PubMed (Medline), Trip Database, Cochrane Library, EMBASE, SUMsearch, and Web of Science. Review Methods: The outcome assessed was the presence of pepsin in LPR patients. We included articles in which pepsin was studied in LPR patients (clinically suspected or with confirmed diagnosis). Studies with no control group, comparison group, and/or a sample size lower than 20 patients were excluded. Results: Twelve studies were included. All included studies, with the exception of 2, found statistically significant differences for pepsin in cases compared with healthy controls. Conclusion: Pepsin might be a reliable marker in LPR patients, although questions remain about optimal timing, location, nature, and threshold values for pepsin testing. Future investigations are necessary to clarify the best method to use pepsin in the diagnostic process of LPR.